Influence of Combined Transcranial Direct Current Stimulation and Motor Training on Corticospinal Excitability in Children With Unilateral Cerebral Palsy - Nemanich, Samuel T.; Rich, Tonya L.; Chen, Chao-Ying; Menk, Jeremiah; Rudser, Kyle; Chen, Mo; Meekins, Gregg; Gillick, Bernadette T. (Frontiers in Human Neuroscience, 2019)
Combined non-invasive brain stimulation and rehabilitation interventions have the potential to improve function in children with unilateral cerebral palsy (UCP), however their effects on developing brain function are not well understood. In a proof-of-principle study, we used single-pulse transcranial magnetic stimulation (TMS) to measure changes in corticospinal excitability and relationships to motor performance following a randomized controlled trial consisting of 10 days of combined constraint-induced movement therapy (CIMT) and cathodal transcranial direct current stimulation (tDCS) applied to the contralesional motor cortex. Twenty children and young adults (mean age = 12 years, 9 month, range = 7 years 7 months, 21 year, 7 months) with UCP participated. TMS testing was performed before, after, and six months after the intervention to measure motor evoked potential (MEP) amplitude and cortical silent period (CSP) duration. The association between neurophysiologic and motor outcomes, and differences in excitability between hemispheres were examined. Contralesional MEP amplitude decreased as hypothesized in 5 of 5 participants receiving active tDCS immediately after and 6 months after the intervention, however no statistically significant differences between intervention groups were noted for MEP amplitude (mean difference = -323.9 µV, 95% CI = [-989, 341], p = 0.34) or CSP duration (mean difference = 3.9 ms, 95% CI = [-7.7, 15.5], p = 0.51). Changes in corticospinal excitability were not statistically associated with improvements in hand function after the intervention. Across all participants, MEP amplitudes measured in the more-affected hand from both contralesional (mean difference = -474.5 µV) and ipsilesional hemispheres (-624.5 µV) were smaller compared to the less-affected hand. Assessing neurophysiologic changes after tDCS in children with UCP provides an understanding of long-term effects on brain excitability to help determine its potential as a therapeutic intervention. Additional investigation into the neurophysiologic effects of tDCS in larger samples of children with UCP are needed to confirm these findings.